2016
DOI: 10.17507/jltr.0702.16
|View full text |Cite
|
Sign up to set email alerts
|

Role of Vocabulary Levels Test (VLT) in Chinese Undergraduate Students’ Comprehension of Textbooks

Abstract: Abstract-Vocabulary knowledge has always been considered crucial in reading comprehension. This paper aims to link Chinese learners' performance on Vocabulary Levels Test (VLT) to the profiling of their textbook so as to draw pedagogical implications on English teaching. The participants were 108 freshmen in Jiangsu University of Technology, China. All of them took part in the VLT, and their English textbook was profiled to see the lexical level of the vocabulary. Results showed that 81.48% of the participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 11 publications
0
16
2
Order By: Relevance
“…Some research has been done on the role of vocabulary size in reading comprehension, yet only a few studies correlated participants' performance on VLT with textbook profiling to investigate whether some pedagogy implications could be found. Liu (2016) reveals the result of VLT and English textbook profiling with Chinese undergraduate students at Jiangsu University of Technology in PRC, China. Her research showed that 81% of the participants had mastered a 2000-word vocabulary, hence most of the students had no significant difficulties in understanding the texts used.…”
Section: Vocabulary Size and Reading Comprehension Relationshipmentioning
confidence: 99%
See 2 more Smart Citations
“…Some research has been done on the role of vocabulary size in reading comprehension, yet only a few studies correlated participants' performance on VLT with textbook profiling to investigate whether some pedagogy implications could be found. Liu (2016) reveals the result of VLT and English textbook profiling with Chinese undergraduate students at Jiangsu University of Technology in PRC, China. Her research showed that 81% of the participants had mastered a 2000-word vocabulary, hence most of the students had no significant difficulties in understanding the texts used.…”
Section: Vocabulary Size and Reading Comprehension Relationshipmentioning
confidence: 99%
“…Some studies have reported the reliability, e.g. 0.94 or 0.91 (Liu, 2016;Read, 2009) and this test has been examined by other experts (Gyllstad, 2007;Teng, 2015;Webb & Sasao, 2013). As the measurement of VLT correlates with the level of reading comprehension, it is used to assess the reading texts chosen for undergraduate students and is the initial input to the teachers about the level of their students' ability before their lessons begins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The result is linear with (Liu 2016) research toward undergraduate students of JiangzuChina. Liu (2016) indicated that no participants had reached the mastery level of the 3000, 5000 and academic word category, but 2000.…”
Section: Introductionmentioning
confidence: 69%
“…Liu (2016) indicated that no participants had reached the mastery level of the 3000, 5000 and academic word category, but 2000. Hence both Rinaldi et al (2013) and Liu (2016) suggest the language learners to explore more approach on vocabulary skill such as vocabulary learning strategies and more independent in learning.…”
Section: Introductionmentioning
confidence: 99%